Diversity Of Dragonfly (Hexapoda: Odonata) Around Universitas Ahmad Dahlan, Campus 4 - Indra Putra, Ichsan Luqmana; Putri, Winda Aulia (Metamorfosa: Journal of Biological Sciences, 2023)
Dragonflies act as predators of pests as well as bioindicators of waters so that their sustainability needs to be preserved. This study aims to determine the diversity of species, characteristics of species, and species of dragonflies which are abundant and not abundant around campus 4 UAD. The sampling location is divided into four, namely rice fields, housing, vacant land and campus areas. Each area has 2 plots measuring 35 x 20 m. Each plot has a subplot 5 measuring 150 m 2 dispersed in the plot. Sampling was conducted at 08.00 - 11.00 WIB and 15.00 - 17.00 WIB. Sampling was done using a net. The caught dragonfly is inserted with papillot paper and its thorax is pressed to death. Dragonflies are then identified to the species level by comparing their morphology with an identification reference book. Abiotic factors measured were temperature and humidity, wind speed, CO, DO and water pH. The results of this study obtained 4 types of dragonflies, namely Pantala flavescens, Orthretum sabina, Sympetrum fonscolombii and Diplacodes trivialis with a low diversity level of 0.36. The most abundant dragonfly species, Sympetrum fonscolombii , was 249 with a dominance index value of 0.74 and the least abundant was Diplacodes trivialis with 10 heads, with a dominance index value of 0.03. The conclusion of this research is that in the area around campus 4 UAD there is a disturbance in the form of land use change which causes a small index of dragonfly species diversity at that location.